Hydrogen-treated, sub-micrometer carbon beads for fast capacitive deionization with high performance stability. (June 2017) - Krüner, Benjamin; Srimuk, Pattarachai; Fleischmann, Simon; Zeiger, Marco; Schreiber, Anna; Aslan, Mesut; Quade, Antje; Presser, Volker
Abstract: Novolac is a low-cost carbon precursor which can be used to derive nanoporous carbon beads in sub-micrometer size. In this study, we introduce this material as a novel electrode material for capacitive deionization (CDI) with high performance stability and superior desalination rate. The polymer beads were synthesized employing a self-emulsifying system in an autoclave, pyrolyzed under argon, and activated with CO2, yielding a specific surface area of 1905 m 2  g −1 with a high total pore volume of 1.26 cm 3  g −1 . After CO2 activation, the material shows a salt sorption capacity of ∼8 mg g −1, but the performance is highly influenced by functional groups, causing an inversion peak and fast performance decay. However, de-functionalization via hydrogen treatment is outlined as an effective strategy to improve the CDI performance. After hydrogen treatment of novolac-derived carbon beads, we obtained a salt sorption capacity of 11.5 mg g −1 with a charge efficiency of more than 80% and a performance stability of around 90% over more than 100 cycles. Particularly attractive for practical application is the very high average salt adsorption rate of 0.104 mg g −1  s −1, outperforming commercial activated carbons, which are commonly used for CDI, by at least a factor of two. Graphical abstract: